The Jurisdiction to Prescribe Provisional Measures by the International Tribunal for the Law of the Sea: Evolving Jurisprudence and Aspects of the Implementation - (:unkn) unknown (My University, 2019)
This article aims to unveil various features of provisional measures, especially under the ITLOS jurisdiction. The jurisprudence of other international courts and tribunals are very essential to understand how ITLOS deals with a request for provisional measures. Therefore, comparing the jurisdiction and jurisprudence of the ITLOS with other courts and tribunals will help to reveal various aspects of the provisional measures.